Ophie's ghosts - Ireland, Justina (Balzer + Bray, an imprint of HarperCollinsPublishers, 2021)
Discovering her ability to see ghosts when a cruel act ends her father's life and forces her to move in with relatives in 1920s Pittsburgh, young Ophelia forges a helpful bond with a spirit whose own life ended suddenly and unjustly.